Progress in Nano-Electro Optics III Industrial Applications and Dynamics of the Nano-Optical System - Ohtsu, Motoichi (Springer Series in Optical Sciences, 2005)
This unique monograph series "Progress in Nano-Electro Optics" reviews the results of advanced studies of electro-optics on the nanometric scale. This third volume covers the most recent topics of theoretical and experimental interest including classical and quantum optics, organic and inorganic material science and technology, surface science, spectroscopy, atom manipulation, photonics, and electronics. Each chapter is written by one or more leading scientists from the relevant field. Thus, high-quality scientific and technical information is provided to scientists, engineers, and students engaged in nano-electro optics and nanophotonics research. The first two volumes addressed the "Basics and Theory of Near Field Optics" (2002) and "Novel Devices and Atom Manipulation" (2003).